Design and test of automatic detection platform for soil fragmentation rate in rotary tillage - Du, Xinwu; Yang, Xulong; Pang, Jing; Ji, Jiangtao (International Journal of Agricultural and Biological Engineering, 2020)
As an important index of soil crushing performance of rotary tiller, the soil fragmentation rate is still limited to manual measurement. In this study, an automatic detection platform for soil fragmentation rate was designed, which integrated soil intake, screening, weighing and calculation of soil fragmentation rate. This platform can solve the problem that the index of the soil fragmentation rate cannot be detected quickly and effectively after rotary tillage, which leads to difficulty in field quality evaluation. The platform was mainly composed of a shovel soil module, conveying module, screening module, weighing module and automatic control system, which could realize single-line and multi-point automatic soil fragmentation rate detection. Based on the homogeneous dry slope model, the tilting angles of soil intake and soil feeding after rotary tillage on the platform were determined to be 30.10° and 26.67°, respectively. According to the principle of flow conservation, a rotary circulation screening module was designed to obtain soil particle size grading. A method based on the principle of multi-line and multi-point measurement was developed to detect soil fragmentation rate. The influence of screening speed on screening effect was analyzed, and the reasonable value of screening speed was determined to be 0.5 m/s. A field performance test was carried out in October 2019 to verify the detection performance of the platform. The results showed that, compared with the manual test method, the maximum test error was no more than 11%, the minimum test error was less than 4%, the maximum single test time was no more than 2 min, and the total test time of each test area was no more than 30 min. The efficiency of single-point detection was significantly better than the manual detection, which indicated that the design in this study met the requirements of rapid detection of soil fragmentation rate, and provided a new idea for the automatic detection of quality of rotary tillage.Keywords: rotary tillage, soil fragmentation rate, automatic detection, design, testDOI: 10.25165/j.ijabe.20201305.5678Citation: Du X W, Yang X L, Pang J, Ji J T. Design and test of automatic detection platform for soil fragmentation rate in rotary tillage. Int J Agric & Biol Eng, 2020; 13(5): 40–49.